2018
DOI: 10.1097/wnr.0000000000001019
|View full text |Cite
|
Sign up to set email alerts
|

The neural underpinnings of music listening under different attention conditions

Abstract: Most studies examining the neural underpinnings of music listening have no specific instruction on how to process the presented musical pieces. In this study, we explicitly manipulated the participants' focus of attention while they listened to the musical pieces. We used an ecologically valid experimental setting by presenting the musical stimuli simultaneously with naturalistic film sequences. In one condition, the participants were instructed to focus their attention on the musical piece (attentive listenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 45 publications
(47 reference statements)
0
13
0
1
Order By: Relevance
“…The attentive music listening program used for training in the current study is different from passive listening to the music one might do in daily life (e.g., doing irrelevant tasks during listening). Neurophysiological studies have reported different brain activations between attentive and passive listening conditions with music materials (Jancke et al, 2018). The differences between passive vs. attentive listening can also be seen in the cortical responses to an oddball paradigm that consists of rarely presented stimuli (deviants) and frequently presented stimuli (standard stimuli).…”
Section: Discussionmentioning
confidence: 99%
“…The attentive music listening program used for training in the current study is different from passive listening to the music one might do in daily life (e.g., doing irrelevant tasks during listening). Neurophysiological studies have reported different brain activations between attentive and passive listening conditions with music materials (Jancke et al, 2018). The differences between passive vs. attentive listening can also be seen in the cortical responses to an oddball paradigm that consists of rarely presented stimuli (deviants) and frequently presented stimuli (standard stimuli).…”
Section: Discussionmentioning
confidence: 99%
“…However behavioral data from some participants suggest that some listeners used continuous measurements as indicators of general emotional intensity instead; although there is little known about individual thresholds of recognizing chills experiences, some continuous data are consistently reflecting some form of experience, and it is highly unlikely that these listeners are experiencing chills throughout the course of the piece. Furthermore, concurrent tasks during music listening may affect the affective experience (Markovic et al, 2017 ; Jäncke et al, 2018 ), although there are some inconsistent results (Hutcherson et al, 2005 ). Regardless, the continuous measurement task was highly simplified, and whilst some emotional intensity may have been lost, the stimuli remained effective elicitors of chills, and the current results and effects of manipulation were clear.…”
Section: Discussionmentioning
confidence: 99%
“…For these continuous measurements, data were collected with an analog slider, moved upwards to indicate higher levels of chills intensity, or vice-versa; slider movement changed amplitude values of a monitored and recorded sine wave, which was preferred over a rating scale, as it was deemed to be less distracting, and a simpler task. It was important to keep this task as simple as possible, as concurrent tasks during listening may have the capacity to affect physiological and emotional responses (Jäncke et al, 2018 ). Chills are normally reported by participants, either by raising their hand to indicate the response (Panksepp, 1995 ; Craig, 2005 ) or by pressing a button (Grewe et al, 2007 ; Salimpoor et al, 2009 ).…”
Section: Methodsmentioning
confidence: 99%
“…They found the theta and alpha oscillations along central and occipital area of scalp topology seems significantly associated with high-level (tonal and rhythmical) acoustic features processing. Also, many other studies tried to examine the neural underpinnings of music listening based on sensorlevel EEG data (Jäncke et al 2015(Jäncke et al , 2018Markovic et al 2017), in which different frequency bands were extracted using time-frequency analysis methods and further analyzed separately (e.g., event-related synchronizations and oscillatory power changes). Those studies showed the influence of different music listening styles on neurophysiological and psychological state interpreted by brain activation.…”
Section: Introductionmentioning
confidence: 99%